DINAMIKA HUKUM NASIONAL SEBAGAI IMPLEMENTASI PERJANJIAN PERDAGANGAN BEBAS ASEAN DAN MITRA - Rahmanto, Imam Basuki (Ensiklopedia Education Review, 2025)
Abstract: This study examines the legal dynamics and regulatory challenges faced by Indonesia in implementing the ASEAN Plus Three (APT) Free Trade Agreement (FTA). Since ASEAN does not have a supranational legal mechanism, legal harmonization relies entirely on the commitments of individual member states. Indonesia has adopted a multifaceted strategy, including agreement ratification, regulatory adjustment, and cross-sectoral coordination, to align domestic laws with regional obligations. The analysis reveals that while Indonesia has established an effective legal framework to comply with its APT commitments, ongoing regulatory reforms are needed to respond to evolving agreements and to ensure domestic benefits. By comparing ASEAN’s approach with other regional integration models, such as the European Union, this study underscores the importance of strengthening institutional capacity and initiative-taking engagement to maximize the benefits of regional trade liberalization. The APT Work Plan 2023–2027 serves as a strategic blueprint to align national policies with regional integration efforts.Keywords: ASEAN, Free Trade Agreement, Legal Harmonization